1990
DOI: 10.1007/bf00328174
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of cadmium, copper, lead, zinc and calcium in the tissues of the earthworm Lumbricus rubellus sampled from one uncontaminated and four polluted soils

Abstract: The tissue distribution of Cu, Cd, Pb, Zn, and Ca in the earthworm Lumbricus rubellus living in non-polluted and heavy-metal polluted soils was investigated. Cd, Pb and Zn were primarily accumulated within the posterior alimentary canal. As the whole-worm Pb burden increased, the proportion of the metal accumulated within this tissue fraction increased. A similar pattern was found for Zn. By contrast, 70%-76% of the Cd burden was found in the posterior alimentary canal, irrespective of the whole-worm Cd conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
52
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 34 publications
9
52
0
Order By: Relevance
“…Streit (1984) proposed a model for the uptake of copper by earthworms including active excretion, which was activated when a critical body concentration was exceeded, while Neuhauser et al (1985) suggested saturation of uptake sites or active regulation of assimilation, being in line with the possibility of a restricted uptake mechanism as proposed by Hopkin (1989). Whatever mechanism resulted in this pattern of lower BCFs of copper at higher soil concentrations, such evidence indicates that earthworms probably manage copper by active regulation, rather than adapt a strategy based on accumulative detoxification (Morgan and Morgan, 1990). Consideration of the relationship between individual earthworm tissue copper concentrations and their neutral-red retention times (i.e., the level of cellular stress) (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Streit (1984) proposed a model for the uptake of copper by earthworms including active excretion, which was activated when a critical body concentration was exceeded, while Neuhauser et al (1985) suggested saturation of uptake sites or active regulation of assimilation, being in line with the possibility of a restricted uptake mechanism as proposed by Hopkin (1989). Whatever mechanism resulted in this pattern of lower BCFs of copper at higher soil concentrations, such evidence indicates that earthworms probably manage copper by active regulation, rather than adapt a strategy based on accumulative detoxification (Morgan and Morgan, 1990). Consideration of the relationship between individual earthworm tissue copper concentrations and their neutral-red retention times (i.e., the level of cellular stress) (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The susceptibility of earthworms to copper may be the result of an inability of most tissues to synthesize Cubinding ligands in response to the presence of the metal. Earthworms most likely manage copper by regulation rather than by accumulative detoxi"cation (Morgan and Morgan, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…80, 160, and 320 mg Cu kg −1 ) was sufficiently elevated to cause the tissue copper concentrations of the earthworm to rise above this critical level, despite the activity of the earthworm regulatory mechanism (BCFs ca. 0.3) (Morgan and Morgan, 1990). The neutral-red retention time corresponding to this critical body copper concentration was calculated as 24, 32, and 24 min and the tissue copper concentration EC 50 for the neutral-red response was 25, 39, and 38 g SVENDSEN AND WEEKS be maintained below the critical level without the need for extensive regulation by the earthworm (BCF ca.…”
Section: Discussionmentioning
confidence: 99%